1985
DOI: 10.1145/3148.3326
|View full text |Cite
|
Sign up to set email alerts
|

Expressions for batched searching of sequential and hierarchical files

Abstract: Abstract:Batching yields significant savings in access costs in sequential, tree-structured, and random files. A direct and simple expression is developed for computing the average number of records/pages accessed to satisfy a batched query of a sequential file. The advantages of batching for sequential and random files are discussed. A direct equation is provided for the number of nodes accessed in unbatched queries of hierarchical files. An exact recursive expression is developed for node accesses in batched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1987
1987
1995
1995

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…Batching has also been studied in terms of physical block accesses. The early work in [10] and recently in [8] derive approximate and exact formulae for the expected number of block accesses for successful searching of sequential and hierarchical files. In [7] new expressions are for partly or completely unsuccessful search of sequential or hierarchical files.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Batching has also been studied in terms of physical block accesses. The early work in [10] and recently in [8] derive approximate and exact formulae for the expected number of block accesses for successful searching of sequential and hierarchical files. In [7] new expressions are for partly or completely unsuccessful search of sequential or hierarchical files.…”
Section: Discussionmentioning
confidence: 99%
“…In the next section it will be shown that formula (6) is a very close approximation of formula (8). Now we will provide a new approximate formula to be used in place of formula (9).…”
Section: P(nr Ql) ~ P(ns Q2) R = O S = O T = O ( N -1 -S -T ) P (mentioning
confidence: 98%
“…B + tree) files. See, for example, Shneiderman and Goodman (1976), Palvia (1985), Lang et al (1989), and Lang and Manolopoulos (1990) under the rubic of 'batch searching' of files. Christodoulakis (1984a,b) discusses block selectivity estimation where records may be clustered together; for instance, if the file is sorted on the attribute used in a selection predicate.…”
Section: Block Selectivity Estimationmentioning
confidence: 99%
“…The advantages of batched searching on databases have been advocated by a number of researchers [1,2,3,4]. The major argument is that by batching searches or updates, the throughput of the system is increased and the potential reduction on processor demand may in fact reduce the response time.…”
Section: Supported By the Office Of Energy Research Us Doe Under Cmentioning
confidence: 99%